Ruptured non-communicating rudimentary horn pregnancy: Case report and literature review - Baykuş, Yakup; Kavak, Salih Burçin; Güngör, Sami; Çelik, Hüsnü (My University, 2012)
Unicornuat uterus with rudimentary horn is the rarest congenital anomaly of the female genital tractus. It causes many obstetric and gynecologic complications. Pregnancy implanting at rudimentary horn is very rare. Risk of uterine rupture is very common during the second trimester of pregnancy due to the weak muscular wall of the rudimentary horn. The uterine rupture can cause life threating bleeding. If early diagnosis and treatment is not made, high mortality rate for both the fetus and the mother can be seen. In this case report, we examined a pregnacy in which fetus is 21 week old when calculated according to the last menstruel period and measuring 18 week old by ultrasonography examining causing a uterine rupture in a non-comminicaty rudimentary horn and discussed the diagnosis and treatment in the light of litherature. Copyright © 2012 by Türkiye Klinikleri.
Rüptüre non-komünike rudimenter horn gebeli?i: Olgu sunumu ve literatürün gözden geçirilmesi
Keywords: Ectopic; Mullerian ducts; Pregnancy; Uterine rupture